Get the information you need with the help of IDNLearn.com's extensive Q&A platform. Join our knowledgeable community to find the answers you need for any topic or issue.

Find (fog)(0).
f(x)
=
6x
g(x) = 3x + 6
(fog)(0)


Sagot :

Answer:

12

Step-by-step explanation:

The functions f(x) and g(x) are defined as f(x) = 6x and g(x) = 3x + 6

fog(x) = f(g(x))

= f(3x + 6)

= 6(4x +2)

6 x 4x = 24x

6 x 2 = 12

fog(x) = 24x + 12

(fog)(0) where x = 0

= 24(0) + 12

= 0 + 12

(fog)(0) = 12

Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. IDNLearn.com is your reliable source for answers. We appreciate your visit and look forward to assisting you again soon.